Role of Social Media Marketing in Business Growth at International Arena: Exploring the Impact of Social Media Marketing in the International Business Landscape (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Social media which is the real backbone of society in terms of entertainment, social gathering, advertising, digital marketing and globalization of business as well. As technology is enhancing regularly it maximizes the use of Social media to business and its consumers. Face book and so many applications are the live example of this. This paper consists of a better understanding of social media thought various definitions, some review studies along with significant advantages of social media for business in international arena.